BIBLIOMETRIC ANALYSIS OF TRANSACTIONS IN E-COMMERCE FROM A SHARIAH ECONOMIC PERSPECTIVE - Syahputra, Hendra; Shintia, Riza; Insani, Muhammad Fitrah (Journal of Sharia Economics, 2025)
Technology development has become an important issue in recent decades. Technology has become an important necessity for humans in life. Like transactions in the market that have adopted technology by creating e-commerce so that transactions become effective and efficient. This study aims to analyze the development of research on e-commerce transactions from an Islamic economic perspective, addressing critical issues such as the integration of shariah principles in digital transactions and the impact of technology on Islamic finance. This research uses a bibliometric approach, utilizing data from scientific databases such as Web of Science and Scopus to identify relevant publications and analyze citation patterns. The methodology includes data collection, processing and descriptive statistical analysis to uncover trends in the literature from 2015 to 2025. Key findings revealed a significant increase in publications, with over 1,000 papers and a total of 1,156 citations, indicating a growing interest in this field. The analysis highlighted a shift towards qualitative research methods, as evidenced by the prevalence of keywords related to user experience and empirical validation. In addition, emerging themes such as sustainability and risk management in e-commerce transactions are gaining traction, reflecting contemporary concerns within an Islamic economic framework. The study concludes that the research landscape is evolving, with each author contributing significantly to the discourse. The interconnectedness of concepts such as fairness, trust and adherence to Shariah principles underscores the need for a comprehensive understanding of consumer behavior in shariah-compliant e-commerce.